Recurrence of atrial fibrillation in dependence of left atrial volume index - Kranert, Malte; Shchetynska-Marinova, Tetyana; Liebe, Volker; Dösch, Christina; Papavassiliu, Theano; Akın, Ibrahim; Borggrefe, Martin; Hohneck, Anna (In vivo, 2020)
Background/Aim: Despite advances in the treatment strategies of patients with atrial fibrillation (AF), the risk of AF recurrences is still over 50%. An increased left atrial volume index (LAVI) reflects left ventricular diastolic dysfunction (DD) and deterioration of the LA function. This study aims to determine AF recurrence following cardioversion (CV) or catheter ablation for AF (pulmonary vein isolation; PVI) in dependence of DD and LAVI. Patients and Methods: One hundred and sixty-two patients with paroxysmal or persistent AF in whom either CV or PVI were performed were included and followed over a mean of 22.9±3.8 months. Recurrence was defined as any recurrence of AF that occurred 3 months following the procedure. DD and LAVI were assessed using transthoracic echocardiography (TTE). Results: Recurrent AF occurred in 100 (61.7%) patients, predominantly following CV [CV 41 (76.2%) vs. PVI 59 (54.6%), p<0.0001]. Both DD and an increased LAVI were more common in the recurrence-group [DD 46.0% vs. 14.5%, p=0.0001; LAVI (ml/m2) 49.0±18.6 vs. 26.3±7.0, p<0.0001]. ROC analysis revealed LAVI>36 ml/m2 as cut-off (p<0.0001, AUC=0.92, 95%CI=0.87-0.97, sensitivity=76%, specificity=94%). In the multivariate analysis, DD (HR=1.6, 95%CI=1.3-2.1, p=0.04) and LA enlargement (defined as LAVI>36 ml/m2 with HR=2.1, 95%CI=1.8-2.7, p<0.0001) could be identified as independent predictors of AF recurrence after attempting to control the heart rhythm. Conclusion: LA enlargement and DD are independent risk factors associated with AF recurrence after initial successful rhythm control attempt. These findings have implications for timing of either ablation or CV.
Gesehen am 22.04.2020